Melatonin and breast cancer: Evidences from preclinical and human studies. (February 2018) - Kubatka, Peter; Zubor, Pavol; Busselberg, Dietrich; Kwon, Taeg Kyu; Adamek, Mariusz; Petrovic, Daniel; Opatrilova, Radka; Gazdikova, Katarina; Caprnda, Martin; Rodrigo, Luis; Danko, Jan; Kruzliak, Peter
Abstract: The breast cancer affects women with high mortality and morbidity worldwide. The risk is highest in the most developed world but also is markedly rising in the developing countries. It is well documented that melatonin has a significant anti-tumor activities demonstrated on various cancer types in a plethora of preclinical studies. In breast cancer, melatonin is capable to disrupt estrogen-dependent cell signaling, resulting in a reduction of estrogen-stimulated cells, moreover, it's obvious neuro-immunomodulatory effect in organism was described. Several prospective studies have demonstrated the inverse correlation between melatonin metabolites and the risk of breast cancer. This correlation was confirmed by observational studies that found lower melatonin levels in breast cancer patients. Moreover, clinical studies have showed that circadian disruption of melatonin synthesis, specifically night shift work, is linked to increased breast cancer risk. In this regard, proper light/dark exposure with more selective use of light at night along with oral supplementation of melatonin may have benefits for high-risk women. The results of current preclinical studies, the mechanism of action, and clinical efficacy of melatonin in breast cancer are reviewed in this paper. Melatonin alone or in combined administration seems to be appropriate drug for the treatment of early stages of breast cancer with documented low toxicity over a wide range of doses. These and other issues are also discussed.